ANALYSIS OF EFFECT OF COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE: STUDY IN PT. XYZ MEDAN - Susi Handayani; Raihanah Daulay (Proceeding International Seminar of Islamic Studies, 2022)
In companies, it is often found that there are employees who come late, are less careful in their work, do not feel enough about their salaries and several complaints related to employee motivation. These problems are closely related to the work results of employees in the company. The purpose of this study was to determine whether compensation and motivation together (simultaneously) or separately (partially) have a significant effect on employee performance at PT. XYZ Medan. This research is a causal associative study using a quantitative approach. The sample in this study amounted to 82 respondents. The data analysis technique used is multiple linear regression. The results showed that compensation and motivation simultaneously had a significant effect on employee performance at PT. XYZ Medan, partial compensation has a significant effect on employee performance at PT. XYZ Medan and motivation partially have a significant effect on employee performance at PT. XYZ Medan.Keywords: Compensation, Motivation, and Employee Performance